STUDY OF HYDRODYNAMICS AND SEDIMENT TRANSPORT IN LOWER CITARUM RIVER IN WEST JAVA PROVINCE - Saurena, Alfandias
The Lamong River Basin is part of the Bengawan Solo River Basin with critical land conditions due to the reduction of forested areas in its drainage area. As the forested areas continue to decrease, surface runoff rates increase, potentially leading to increased land erosion rates. Increased land erosion leads to higher sedimentation rates discharged into the river, reducing the river's capacity to hold water. Therefore, understanding the relationship between changes in land cover and flooding around the Lamong River is crucial. The study conducted in this research includes hydrological analysis, an assessment of the existing capacity of the Lamong River, an analysis of Lamong River floods, an analysis of land erosion and sedimentation rates, and an analysis of morphological changes resulting from flood control construction in the Lamong River. Hydrological analysis was carried out using the HEC-HMS application, capacity and flood condition analysis with the HEC-RAS application, land erosion analysis using the USLE method, and morphological change analysis with the assistance of the HEC-RAS application. Flood condition analysis was conducted for three flood recurrence intervals: 5 years, 10 years, and 25 years. Morphological change analysis was conducted for two scenarios after simulating changes in the riverbed for seven years of calibration: one scenario with levee construction and one without levee construction, using daily discharge for ten years of simulation. Based on the simulation results for flood conditions, the Lamong River can collect a peak flood discharge of more than 700 m3/s, while its current capacity can only accommodate a discharge of 200 m3/s. The 5-year flood discharge (Q5) for the Lamong River is 610 m3/s, the Q10 discharge is 799.74 m3/s, and the Q25 discharge is 980 m3/s respectively. For various recurrence intervals, overflow depths range from 0.6 m to 2.7 m, occurring in the middle and downstream of the Lamong River. Overall, the soil erosion value in the Lamong River Basin is 102,213.05 m3/ha/year, and the sediment volume is 16,559.99 m3/year. The sedimentation modeling results from 2012 to 2021 predict an accumulation of riverbed changes totaling 357,976.64 tons, or approximately 35,797.66 tons per year.